Exploring the challenges and possibilities of online assessment amidst the Covid 19: Perspectives from Bangladesh - Farzana, Farha (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2020.